(untitled) (Research, Society and Development, 2020)
The process of transsexualization in children and adolescents represents a social anathema that develops from early diagnoses, bumping into medical, ethical and legal issues. Thus, the present study analyzes the legislation aimed at the care of transgender individuals in Brazil, as well as analyzes the fourth generation of human rights and bioethics in light of the moral philosophy of transexualizing therapies and therapies for children and adolescents. In the end, the theory of gender is commented on according to concepts amplified by the media, as opposed to the Crip and Queerness Theory, currently in diffusion.